Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Transformasional-Transaksional terhadap Kinerja Karyawan melalui Komitmen Organisasi dan Kepuasan Kerja pada Yayasan Nurul Hayat - Muhammad Yusuf Aria Widjaja; Mukhamad Yasid; Abdurrahman Misno (Universitas Negeri Surabaya, 2018)
Cultural organisation as a system formed by the company management, has the same characteristics than other organisations. It is due to the leader has authority to change the old paradigm to a new transformation. The purposes are employees have a high commitment in organisation, satisfaction at work, and also to improve the performance of the given contribution. The purpose is to examine the Influence of Cultural Organisation and a leader style which is Transformational-Transactional sign to Employee Performance, High Commitment in Organisation, and also the satisfaction at work.. This study applies Structural Equation Modeling (SEM) with 5% alpha significance. Data is obtained from 116 employees œNurul Hayat Foundation with proportional sampling technique by using questionnaires, interviews and documentation. At P-Value (> 0,05) and T-Value (> 1,96) indicate that, Culture Organisation has positive and significant influence on employee performance, organisation commitment and job satisfaction. The leadership style has positive and significant influences on job satisfaction and organisation commitment. The leadership style has positive and insignificant effects on employee performances. Organisation commitment has positive and insignificant effects on employee performances. Job satisfaction has positive and significant effects on employee performances.